Evaluating the Impact of Drone Technology Bootcamps on Student Skill Development and Performance - Ravichandran, R (Journal of Vocational Education Studies, 2025)
This study evaluates the impact of a comprehensive drone technology bootcamp conducted at PSSCIVE Bhopal, targeting school students from diverse educational and demographic backgrounds. Designed to blend theoretical instruction with hands-on drone assembly and flight training, the bootcamp aimed to foster technical skills, innovation, and entrepreneurship awareness. A mixed-methods approach using pre- and post-test assessments, observations, and feedback surveys was employed to analyse learning outcomes. Findings revealed significant improvements in students' theoretical understanding, practical proficiency, and entrepreneurial mindset. Students from various school types, Demonstration Multipurpose Schools, Jawahar Navodaya Vidyalayas, and State Government schools, benefited equally, with marked gains across gender and rural-urban segments. Participants reported increased confidence in knowledge retention and a sustained interest in further exploring drone technology. Despite some technical and logistical challenges, the program successfully addressed gaps in STEM and vocational education by offering an engaging, real-world learning experience. The study underscores the potential of immersive, skill-based bootcamps in enhancing design thinking, innovation, and job readiness among school students. It provides key recommendations for future bootcamp models, including tailored content, continuous assessment, and stronger entrepreneurship modules, thereby supporting NEP 2020’s vision of a holistic and practical education framework.